وحدة مقترحة قائمة على معايير اختيار الآيات القرآنية وتفسيرها في مادة التربية الإسلامية لتنمية مهارات فهم النص القرآني وأثره على إدارة الذات لدى تلاميذ الصف الخامس الابتدائي الصم - عيد، أيمن عيد بكري محمد (جامعة بني سويف - كلية علوم ذوي الاحتياجات الخاصة, 2021)
اهتم التربويون وواضعو المقررات الدراسية بربط التلاميذ وتدعيم صلتهم بكتاب الله عز وجل وخاصة من خلال مقررات التربية الإسلامية، باختيار الآيات القرآنية في المراحل التعليمية المختلفة، لتنمية مهارات فهم النص القرآني تحليلا وتذوقا وتطبيقا واستخلاصا لأحكامه الشرعية، وبما يفيد التلاميذ العاديين وذوي الاحتياجات الخاصة ومنهم الصم عمليا في إدارة ذاتهم وقدراتهم الخاصة، لتحقيق أهدافهم وتنمية مهاراتهم. أسئلة البحث يجيب البحث الحالي عن السؤال الرئيسي التالي: ما فاعلية وحدة مقترحة في ضوء معايير اختيار الآيات القرآنية وتفسيرها في تنمية مهارات فهم النص القرآني وإدارة الذات لدى تلاميذ الصف الخامس الابتدائي الصم؟ أهداف البحث: يهدف البحث الحالي إلى: إعداد معايير اختيار الآيات القرآنية وتفسيرها لدى تلاميذ الصف الخامس الابتدائي الصم، وإعداد وحدة دراسية في ضوء هذه المعايير بهدف تنمية مهارات فهم النص القرآني وتنمية مهارة إدارة الذات لدى التلاميذ الصم. أدوات البحث ومواده: اختبار في مهارات فهم النص القرآني، ومقياس إدارة الذات، ومعايير اختيار الآيات القرآنية وتفسيرها لدى تلاميذ الصف الخامس الابتدائي الصم، وحدة دراسية مقترحة في ضوء معايير اختيار الآيات القرآنية وتفسيرها لدى تلاميذ الصف الخامس الابتدائي الصم. أهم نتائج البحث: تم استخدام برنامج SPSS لمقارنة نتائج التطبيق القبلي والبعدي لأدوات البحث على العينة التجريبية (9 تلاميذ) والضابطة (10 تلاميذ) من تلاميذ الصف الخامس الابتدائي الصم، ومن أهم النتائج التي توصل إليها البحث: يوجد فرق ذو دلالة إحصائية بين الأداءين القبلي والبعدي للمجموعة التجريبية عند مستوى دلالة (0.05) لصالح التطبيق البعدي في اختبار مهارات فهم النص القرآني وفي مقياس إدارة الذات.
The curriculum developers have been interested in linking students and strengthening their connection with the Qur’an through Islamic education curricula, by choosing Qur’anic verses in different educational stages. To develop the skills of understanding the Qur’an text, in analyzing, tasting, applying, and extracting its legal rulings, as well as for the benefit of ordinary students and those with special needs, including the deaf, in practical management of themselves and their special capabilities; To achieve their goals and develop their skills. Questions of the research: The Current research try to answers the following main question: What is the effectiveness of the suggested unit in light of the standards of choosing the Quran verses and interpreting them in developing the skills of understanding the Quran text and self-management of the fifth primary deaf students? Aims of the research: The current research aims at: preparing the standards of choosing the Quran verses and interpreting them for the deaf of fifth primary students, and preparing a study unit in light of these standards to develop the skills of self-management of the deaf students. Research tools: Test of understanding the Quran text skill, Scale of self-management, Standards of interpretation of the Holy Quran, and choosing the Quran verses for fifth primary deaf students, Suggested study unit in light of standards of choosing the Quran verses and interpreting them for the fifth primary deaf students. The research results: The spss program was used to compare the results of the pre and post application of the research tools on the experimental sample (9 students) and the control sample (10 students) of the fifth grade deaf primary students.: and the result revealed that: There is a statistical difference between the pre and post performance of the experimental group in the (0, 05) level for the fifth grade primary students in favor of the post test of the understanding the Quran text skill test and scale of the self-management.
Keywords: الآيات القرآنية -- النصوص القرآنية -- التربية الاسلامية -- القرآن الكريم